2020
DOI: 10.1186/s12944-020-01257-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity, sedentary behaviours and sleep duration with cardiovascular diseases and lipid profiles: a Mendelian randomization analysis

Abstract: Background Observational studies have shown that moderate-to-vigorous physical activity (MVPA), vigorous physical activity (VPA), sedentary behaviours, and sleep duration were associated with cardiovascular diseases (CVDs) and lipid levels. However, whether such observations reflect causality remain largely unknown. We aimed to investigate the causal associations of physical activity, sedentary behaviours, and sleep duration with coronary artery disease (CAD), myocardial infarction (MI), stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 45 publications
(53 reference statements)
0
52
0
2
Order By: Relevance
“…With the application of MR approach, associations between sleep duration and coronary artery disease (CAD), myocardial infarction (MI), and stroke have been demonstrated. Daghlas et al (2019) supported short sleep duration as a potentially causal risk factor for CAD and MI, whereas Zhuang et al (2020) found no significant association between sleep duration with stroke. The aims of the current study were to estimate the effects of genetically determined sleep duration on the risk of AF and HF with MR analysis.…”
Section: Introductionmentioning
confidence: 94%
“…With the application of MR approach, associations between sleep duration and coronary artery disease (CAD), myocardial infarction (MI), and stroke have been demonstrated. Daghlas et al (2019) supported short sleep duration as a potentially causal risk factor for CAD and MI, whereas Zhuang et al (2020) found no significant association between sleep duration with stroke. The aims of the current study were to estimate the effects of genetically determined sleep duration on the risk of AF and HF with MR analysis.…”
Section: Introductionmentioning
confidence: 94%
“… 21 , 22 , 23 , 24 , 25 Meanwhile, Mendelian randomization (MR) design utilizing valid instrumental variants has been applied as a robust approach to making causal inference. 26 , 27 , 28 , 29 , 30 In our study, we implemented a two-sample MR design to investigate the role of physical activity in 3 common neurodegenerative diseases: AD, PD, and ALS.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that a high or moderate level of PA was protective against stroke in men not women [ 13 ]. In addition, a study found that vigorous physical activity (VPA) was associated with a lower chance of having a stroke compared with light physical activity (LPA) [ 14 ], whereas other research has shown that VPA did not decrease the risk of stroke [ 15 ]. Meanwhile, there were also some inconsistent results in several studies about the associations between the frequency of PA and the risk of stroke [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%